LINGUOCULTURAL ASPECTS OF SIMILES IN ENGLISH AND UZBEK PROVERBS - Ikromova Shakhlo Zakirovna (International Journal of Literature and Language Studies, 2026)
Proverbs are an essential component of a nation's cultural heritage, reflecting the wisdom, beliefs, traditions, and worldview of its people. Similes, as one of the most expressive stylistic devices, frequently appear in proverbs to create vivid imagery and convey moral lessons effectively. This article examines the linguocultural aspects of similes in English and Uzbek proverbs, highlighting their semantic, cultural, and cognitive features. Through comparative analysis, the study reveals both universal human values and culture-specific characteristics embedded in similes. The findings demonstrate that while English and Uzbek proverbs share common conceptual patterns, they differ significantly in the cultural symbols and images used to express similar ideas.